Grappling with ambiguity and contradiction: an examination of the role of reflexivity in coach education research - Crocket, H. (Sports Coaching Review, 2017)
In this article, I analyse the complex process of developing a beginner coach education programme for ultimate Frisbee (ultimate) in collaboration with New Zealand Ultimate and volunteer coaches within New Zealand`s ultimate community. I construct a reflexive account of this participatory action research project, which sought to generate pedagogically informed coach education that would benefit New Zealand`s ultimate community and meet Sport New Zealand`s coaching policies. I focus on particular contextual challenges and opportunities, such as ultimate`s lack of resourcing, and SportNZ`s Coach Development Framework, and, in a reflexive manner, consider how my biography impacted this project.